Role of gut microbiota in the pathogenesis of type 2 diabetes mellitus (literature review) - Koval, S.M.; Snihurska, I.O. (Medicni Perspektivi, 2021)
Type 2 diabetes mellitus is an extremely common disease that leads to the development of life-threatening complications but its pathogenesis remains poorly understood. One of the promising directions in this area is the study of disorders of gut microbiota. Literature data indicate that a number of quantitative and qualitative changes in the composition of the gut microbiota are the most important factors in the pathogenesis of type 2 diabetes mellitus. Bacteria of the genera Ruminococcus, Fusobacterium and Blautia are most involved in the pathogenesis of this disease. The participation of the gut microbiota in the pathogenesis of type 2 diabetes mellitus is due to its metabolites, which play an important role in the regulation of the permeability and integrity of the intestinal wall, the expression of specific intestinal receptors, incretin secretion, gluconeogenesis activity, chronic subclinical inflammation, and even in adipose tissue remodeling. Further in-depth study of gut microbiota disorders is promising in order to develop fundamentally new approaches to the treatment and prevention of type 2 diabetes mellitus.